MANAJEMEN INTERNALISASI PROFIL PELAJAR PANCASILA DI SMP PANGUDI LUHUR DOMENICO SAVIO - Maria Amelia; Tri Joko Raharjo; Noor Hudallah; Fakhruddin; Arief Yulianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to examine how the management of the internalisation of the Pancasila Student Profile at Pangudi Luhur Domenico Savio Junior High School consists of planning, implementation, and supervision. This research uses a qualitative method with a descriptive approach. The data collection techniques used are interviews, observations and document stufdi. Data validation is done by triangulating sources and techniques. The data collected will be analysed using the Miles and Huberman flow model, namely reduction, data display, and conclusion / verification. The results showed that the planning for the internalisation of the Pancasila Learner Profile at Pangudi Luhur Domenico Savio Junior High School goes through a process that includes adjusting the planning with the guidelines issued by the Ministry of Education and Culture, planning is carried out in an annual work meeting, and socialising the school curriculum to parents. Internalisation of the Pancasila Learner Profile is integrated into all school activities, namely classroom learning activities, activities of the Pancasila Learner Profile Strengthening Project (P5), extracurricular activities, and habituation as well as the school's annual program. Internalisation of the Pancasila Learner Profile is carried out with the supervision of all school parties starting from overall supervision by the principal, and supervision in the field by educators. The condition of character education at Domenico Savio Junior High School based on research can be said to be effective because the school makes various efforts and strategies. Character education is implemented by combining the dimensions of the Pancasila Learner Profile with the values adopted by the school.